2020
DOI: 10.1186/s12884-020-2844-z
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, and use of labour pain relief methods and associated factors among obstetric caregivers at public health centers of East Gojjam zone, Amhara region, Ethiopia: a facility based cross- sectional study

Abstract: Background The study was conducted in public health centers of East Gojjam Zone, Amhara region, Ethiopia. The purpose of this study was to assess knowledge, and use of labour pain relief methods and associated factors among obstetric caregivers in the study setting. Methods A facility-based cross-sectional study design was conducted from March 1–30, 2018. The study was conducted among three hundred and nine sampled obstetric caregivers. Structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
53
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(73 citation statements)
references
References 16 publications
10
53
9
1
Order By: Relevance
“…In addition, having adequate knowledge was associated with utilization of labor analgesia. This is similar with studies conducted in Nigeria and Ethiopia [ 15 , 23 ]. However, it is inconsistent with study performed in Kembata Tembaro Zone, Southern Ethiopia, which reported obstetric care providers with inadequate knowledge were practicing labor analgesia more likely [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, having adequate knowledge was associated with utilization of labor analgesia. This is similar with studies conducted in Nigeria and Ethiopia [ 15 , 23 ]. However, it is inconsistent with study performed in Kembata Tembaro Zone, Southern Ethiopia, which reported obstetric care providers with inadequate knowledge were practicing labor analgesia more likely [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…In line with findings from previous studies, providers with more years of experience were more likely to utilize labor analgesia [ 23 , 29 ]. This may be due to the reason that as obstetric care providers became more experienced, their level of knowledge and attitude became improved [ 30 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, other non-pharmacological approaches such as education for childbirth preparation, warm bath/shower and music which can be effectively used in our context were not reported by any of participants signifying limited awareness or rare use of these methods among our participants. This is not unique to Tanzania, similar ndings have been reported in other studies where many methods of nonpharmacological pain relief are not well known by the majority of health care providers, thus unable to offer non-pharmacological methods to manage labour pain [2,12,21,23]. This shows that the use of non-pharmacological methods by health care providers is still low and the management of labour pain is not evidence-based [12,24].…”
Section: Discussionsupporting
confidence: 52%
“…However, undertreating labor pain has been raised as a common issue in similar settings. A study from Ethiopia reported that pain medications were used for labor and delivery in only 34% of patients [ 33 ]. In Nigeria, a study examining pain in women in labor found that they reported having severe pain and would be interested in pain relief during labor if available [ 34 ].…”
Section: Discussionmentioning
confidence: 99%